Participatory planning and investment in climate smart agriculture to reduce risks for small-scale farmers in Central American coffee landscapes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In this CCAFS project, we stimulate partnerships between farmer cooperatives and professionals from public, private and civil society spheres and couple participatory adaptation planning with the development of incentive and investment plans. In this way, we aim to establish a virtuous cycle of investment and adoption of cost-effective Climate Smart Agriculture (CSA) practices in coffee landscapes. This approach will be tested in collaboration with the farmer cooperatives ASOBAGRI in Huehuetenango Guatemala and the PROODECOP in the dry corridor of Nicaragua.